2016
DOI: 10.1080/13562517.2016.1184139
|View full text |Cite
|
Sign up to set email alerts
|

‘ … But we are academics!’ a reflection on using arts-based research activities with university colleagues

Abstract: Arts-based practices, although familiar in some areas of educational research have the capacity to surprise and to shock: they hold promise but also pose risks. In this essay we introduce arts-based research practices and in particular cut-up and collage. We invite readers to reflect on our experiences of arts-based educational research activities with a group of academic colleagues. We describe what we did, what went wrong, what went right and what we learned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…My reflexive exercise in the doctoral class had a transformative impact on me [51][52][53][54][55]. It helped me to discover my true selfhood and to explore the qualitative inquiry approach.…”
Section: Discussionmentioning
confidence: 99%
“…My reflexive exercise in the doctoral class had a transformative impact on me [51][52][53][54][55]. It helped me to discover my true selfhood and to explore the qualitative inquiry approach.…”
Section: Discussionmentioning
confidence: 99%
“…This aesthetic-oriented paradigm has a strong focus on reflexivity and empathy oriented through the creation and consumption of the art (Dunlop, 2001). As such, through this project, like other ABER-oriented projects (Burge et al, 2016;Burnard et al, 2017;Lynch & Glass, 2020) the act of creation and the created product itself served as data. At the outset, participants were invited to join a research project entitled the "arts of resistance research".…”
Section: Methodsmentioning
confidence: 99%
“…To this end, the current researchers made an exerted effort to create an atmosphere of power quality between the researcher and the participants as proposed by Karnieli-Miller et al (2009) through the creation of a nonthreatening and welcoming environment decided upon by the respondent. Arts-based research by Burge et al (2016), similarly conducted among academics at a tertiary institution, found that academics, with their own research background, had certain assumptions about what is appropriate and expressed fears about losing their authority and dignity. In recognizing the established hierarchy in academia, data collection for this study was conducted by the most junior member, rather than the most senior members, of the research team to ensure that participants did not feel intimated or uncomfortable sharing their experiences with an individual who had successfully navigated the academic career hierarchy under investigation.…”
Section: Methodsmentioning
confidence: 99%